STUDY OF SPATIAL PADDY CROP EVAPOTRANSPORATION USING LANDSAT-7 SATELLITE IMAGES AND PENMAN-MONTEITH METHOD ON PLANTATION AREA IN CIASEM, SUBANG - HASTARA AJI (NIM:12809031), ADAM
Evapotranspiration holds an important role in hydrology cycle to measure crop water requirement in agriculture area. On each stages of crop growth, it is Important to know how much water required for the crop to ensure it grows well. It is also helpful for the enhancement of crop productivity and water treatment efficiency in agriculture sector, especially in the dry season. The method people commonly used for finding crop evaporations value only able to give estimation point value around the observed area, despite giving exact evapotranspiration value according to the dimension, time, and crop species variables. Therefore it is needed to find spatial value of crop evapotranspiration. In this study, remote sensing method and surface energy balance were applied to Landsat-7 satellite images to find spatial value of crop evapotranspiration in Ciasem, Subang on April 2002 to September 2002. Through surface energy balance model, Landsat-7 satellite images gave information about net radiation value, soil heat flux, and sensible heat flux. Three of them are the important values to calculate evaporative fraction value which further would be used for finding crop evapotranspiration value. To compare the value, this study also applied Penman-Motheith method in calculating crop evapotranspiration. The images of Landsat-7 satellite been processed through surface energy balance model gave result that crop evapotranspiration values were not evenly distributed for each plantation area in Ciasem, Subang. To area with the same crop species, the crop evapotranspiration value tends to be approximately equal. Yet, the values of crop evapotranspiration between the calculation through remote sensing method and Penman-Monteith method were found to be different. It is because each method uses different variable/factor to be included in the calculation to see how particular crop species relates to evapotranspiration process, net radiation,soil heat flux, and sensible heat flux.